Impact of planting date and density on growth of maize in Northern Iran - Mokhtarpour, Hassan (2011)
Planting date and density are two major factors affecting maize growth and yield. Although many worldwide studies were done to evaluate the effect of planting date and density on maize, it is still necessary to do more studies to add the knowledge in this area because environmental factors affect planting date and density. During the last four decades, many simulation studies were conducted to evaluate maize growth. A robust simulation model can help researchers to understand, predict and control a system. Despite the importance of modeling studies on maize, no simulation study was done in Golestan-Iran. The purpose of this study was to investigate maize growth and yield response to planting date and density in field and simulation studies in Golestan-Iran. The field studies were conducted at the Agricultural Research Center of Golestan, Iran in 2007 and 2008. In the first experiment, the effects of eight planting dates and three planting densities (0.16, 4.5, and 6.5 plants m-2) were investigated in 2007. The experiment was replicated in 2008 by adding another planting density (8.5 plants m-2). In the second xperiment, maize yield response to a wide range of planting densities (0.16, 2.5, 4.5, 6.5, 8.5, 10.5 and 12.5 plants m-2) was evaluated for two seasons in 2008. In the third study, empirical equations were developed to estimate leaf area and leaf weight using the data from different treatments of the first experiment in 2008. Simulation studies were done using two specific maize models: CERES-Maize and IXIM. To calibrate the models, the data of the first five planting dates in optimum planting densities (6.5 plants m-2) from the first field experiments in 2007 were used. Using stepwise approach and sensitivity analysis, genetic coefficients were calibrated for both models. To evaluate the accuracy of the models, the data from different treatments from the first and second experiments in 2008 were used. The models’ validity was tested using three goodness of fit indicators namely, root mean square error, index of agreement (d) and mean error. Results of the first experiment showed planting date, planting density and the interaction between them had significant effect on yield and yield components. The highest yield was produced in the first planting date (10659 kg ha-1). The best planting density among early and middle planting dates was 6.5 plants m-2 while for late plantings no significant differences were observed in yield among the different planting densities. Results of the second experiment showed that in the first season the highest yield was observed in planting density 6.5 plants m-2 (9470 kg ha-1). However, in the second season, no significant difference in yield was observed among the different planting densities (~4500 kg ha-1). Empirical equations were fitted to the observed data to show the relationship of each of the parameters, yield, total dry matter (TDM), leaf area index (LAI) and harvest index (HI) to planting density. Results of the third study showed that the empirical equations developed to estimate leaf area, fresh weight and dry weight could predict their values with a high degree of accuracy in different situations. The results of simulation study showed that both CERE-Maize and IXIM models predicted days to anthesis, days to physiological maturity, LAI, and kernel weight with high accuracy in different planting dates and densities although the IXIM showed a better performance comparing to CERES-Maize model. IXIM model simulated TDM, kernel number and yield with higher accuracy comparing to CERES-Maize model in the first five planting dates. However, both models could not give accurate predictions of these traits in the last three planting dates. Evaluating response of CERES-Maize and IXIM models to planting density showed that both models could predict different traits accurately in the middle planting densities (4.5-8.5 m-2). However, both models verestimated most traits in high planting densities (10.5-12.5 plants m-2). In conclusion, maize should be planted in early planting dates with planting density 6.5 plants m-2 in Golestan-Iran. However, to obtain high yield in late planting dates, planting density should be decreased to 4.5 plants m-2. In simulation study, both models could not predict yield and yield component with high accuracy in the late planting dates and high planting densities therefore, it seems some modification are needed to be done in the functions that calculate daily crop growth rate, kernel number m-2, and LAI. These modifications may improve the accuracy of the models to estimate these traits.